Physico-chemical and Plankton Analysis of Ambuwaya Lake in Kiangan, Ifugao, Philippines - Hoggang, Cheryl Grace B.; Reyes, Alvin T. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Ambuwaya lake is a body of water sustained by groundwater. Dissolved oxygen (5.04±0.70 ppm), pH level (8.19±0.18) and total ammonia-nitrogen (0.11±0.09 ppm) of the lake were within the set standard of the Department of Environment and Natural Resources. However, lake temperature of 33.79±2.91°C was not within the set standard but still tolerable for tilapia and carp available in the lake. The secchi disk visibility reading of 34.58±3.60 cm suggested that the lake was hypereutrophic. The lake total dissolved solids were 45.56±1.04 ppm. Alkalinity level (29.60±3.32 ppm) of the lake was within the set standard by Australian and New Zealand Environment Conservation Council. Fifteen taxa of plankton from eight major groups were identified. Phylum Dinoflagellate had the highest abundance with the dominance of Peridinium sp. The diversity of phytoplankton and zooplankton was very low. Phytoplankton evenness was categorized as a stable community while zooplankton was categorized as an unstable community. The pollution index using the Palmer's index scored 16 indicating the high organic pollution of the lake. Further research study which includes the wet and dry seasons through monthly sampling was recommended to establish water quality in both seasons.